2013
DOI: 10.1123/ijspp.8.6.671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ischemic Preconditioning on Land-Based Sprinting in Team-Sport Athletes

Abstract: Results from the current study suggest there to be no benefit to team-sport players in using IPC as a means of enhancing sprint performance over a distance of 30 m. While IPC has been shown to be beneficial to sprint activities in other sports such as swimming, further research is required to elucidate whether this is the case over distances associated with land-based events in track and field or in events reliant on repeated-sprint ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 26 publications
8
53
2
3
Order By: Relevance
“…This pressure is supported by similar IP literature (Bailey, Jones, et al 2012;de Groot et al 2010;Sharma et al 2015), however recent near infrared spectroscopy data indicates arterial pulses may be observed up to 300 mmHg (Kido et al 2015). Pilot data, collected using Doppler ultrasound, as well as published literature (Gibson et al 2013), identified 50 mmHg as an appropriate control pressure, as it provides a sensation of pressure, without impairing arterial flow.…”
Section: Ischaemic Preconditioningsupporting
confidence: 58%
“…This pressure is supported by similar IP literature (Bailey, Jones, et al 2012;de Groot et al 2010;Sharma et al 2015), however recent near infrared spectroscopy data indicates arterial pulses may be observed up to 300 mmHg (Kido et al 2015). Pilot data, collected using Doppler ultrasound, as well as published literature (Gibson et al 2013), identified 50 mmHg as an appropriate control pressure, as it provides a sensation of pressure, without impairing arterial flow.…”
Section: Ischaemic Preconditioningsupporting
confidence: 58%
“…Research investigating the effect of IPC on exercise has included measures of aerobic capacity (Crisafulli et al, 2011;De Groot et al, 2010), speed (Gibson, White, Neish, & Murray, 2013) and recovery following strength and power tasks (Beaven et al, 2012). Data from these studies are equivocal with the suggestion that a pattern of responders and non-responders may exist and that the intervention may be less effective in female populations (Beaven et al, 2012;Gibson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, the results are equivocal. Several studies found an improvement in exercise performance, i.e., time to failure (time trial performance), peak power output, and repetitions, to name a few, after IPC on the primary or a part of the engaged limbs 4,8,[10][11][12][13][18][19][20][21]26) , whereas other studies did not show any beneficial effects [5][6][7]9,10,[14][15][16][17]22,24,25) . A few studies investigated the effects of remote IPC on exercise performance.…”
Section: Ipc Protocolmentioning
confidence: 99%
“…Further, the numbers of ischemic-reperfusion cycles were also varied in previous studies. For example, one study used 2×5 min cycles 8) , nine studies used 3×5 min cycles 5,7,10,[12][13][14]18,23,26) and 13 studies used 4×5 min cycles 4,6,9,11,[15][16][17][19][20][21][22]24,25) . As a result, a manipulation of 2 cycles showed improvement of exercise performance (100%), seven of nine studies using 3 cycles also showed improvement of exercise performance (78%), whereas, only five of 13 studies using 4 cycles showed positive effects with IPC (38%).…”
Section: Ipc Protocolmentioning
confidence: 99%
See 1 more Smart Citation